Quality Assurance System Policy Evaluation Strategy to Increase the Competitiveness of Private Universities - Agus Supriatna; Benyamin Harits; Yaya Mulyana Aziz (Kolaborasi : Jurnal Administrasi Publik, 2023)
The purpose of this study was to find out and analyze how the higher education quality assurance system works and to find out and analyze the dimensions of quality assurance system policy evaluation to improve the competitiveness of private tertiary institutions in the city of Bandung. This study uses a descriptive analysis method with a qualitative type and is supported by the SWOT technique. The results of the study show that the implementation of the quality assurance system for Private Higher Education in Bandung City is still not effective, so a policy evaluation is needed through (1) Administrative evaluation by taking into account: Effort evaluation, performance evaluation, adequacy of performance, efficiency evaluation and process evaluation, (2) Judicial evaluation by taking into account: Issues of legal validity, possible violations of the constitution, possible violations of the legal system, possible violations of ethics and state administration rules, (3) Political evaluation by taking into account: Political process in determining policies, acceptance of political constituencies towards public policies, implementation information technology. The results of the policy evaluation in this study then produce recommendation strategies related to the implementation of the Higher Education quality assurance system by the government's standard provisions.